A CAUSAL RELATIONSHIP MODEL OF FACTORS INFLUENCING TO EFFIENCY OF SCHOOL ADMINISTRATION IN THE DIGITAL TECHNOLOGY ERA - Koonsorn, Sathit; Dajong, Yanin; Phongsai, Duanchai; Chankong, Panyarat (Journal of MCU Nakhondhat, 2023)
The objectives of this research were 1) to create a causal relationship model of factors influencing to efficiency of school administration In the digital technology era and 2) to examine the congruence with the causal relationship model of factors influencing to efficiency of school administration in the digital technology era by developing with the empirical data. This research was mixed methods approach : qualitative and quantitative research design.The study was conducted in 2 phases. The first phase was the conceptual framework construction by a study of document involved, researches and focus group discussion of specialists.The second phase was the hypothesis verification by using questionnaire with five rating scale at the reliability of 0.95. The research was carried out with 310 personnel samples of schools of Secondary Educational Service Area Office Nongkhai which were 31 school directors and 279 teachers by purposive sampling. The statistic used for analyzing basic data and confirmatory factor analysis:CFA and congruence analysis between hypothesis model and empirical data was computer program. The research findings found as follows: 1) The developed causal relationship model of factors influencing to efficiency of school administration in the digital technology era consisted 4 components of digital technology leadership, digital technology management, digital technology planning, and digital technology culture. 2) The results of examining the model developed was congruent with empirical data by considering was 221.19 at df 168, p - value was 0.14, GFI value was 0.96, AGFI value was 0.94, RMSEA value was 0.03. Total of variables as the developed model, it could explain variance of effiency of school administration in the digital technology era, for 68% at .05 significant level.